Quantifying the performance of a passive deaerator in a gas-fired closed loop domestic wet central heating system. (May 2017) - Johnston, David; Glew, David; Miles-Shenton, Dominic; Benjaber, Moaad; Fitton, Richard
In the UK, approximately 16% of the energy use can be attributed to domestic wet central heating systems. Government financial support and advances in technology have led to boilers becoming more efficient and a range of technologies are now available that claim to be able to improve the efficiency of domestic wet central heating systems. One such low cost technology is a passive deaerator. This article presents the results obtained from installing a passive deaerator on the closed loop of a gas-fired wet central heating system, under controlled conditions in the Salford Energy House. The results indicate that although marginally less heat output was required from the boiler when the passive deaerator was operating, these savings are more or less out weighted by the boiler short cycling more frequently. Consequently, the overall reduction is gas consumption achieved by utilising the passive deaerator device is only of the order of 0.5%; this scale of savings may just be a consequence of measurement noise. The implications are that although a marginal benefit may be attributed to these products, if short cycling takes place, then these savings may become insignificant. Practical application: This article describes a test method that has been used to quantify the energy savings that could be achieved by installing a passive deaerator on the closed loop of a wet central heating system. Although the results indicate that the energy savings associated with using such a device are likely to be marginal, the test method described could be used to test a range of other devices that claim to improve the performance of domestic wet central heating systems, to directly compare before and after performance.